High Energy Density Supercapacitors: An Overview of Efficient Electrode Materials, Electrolytes, Design, and Fabrication - Pathak, Mayank; Bhatt, Diksha; Bhatt, Rajesh Chandra; Bohra, Bhashkar Singh; Tatrari, Gaurav; Rana, Sravendra; Arya, Mahesh Chandra; Sahoo, Nanda Gopal (Chemical record, 2024)
Supercapacitors (SCs) are potentially trustworthy energy storage devices, therefore getting huge attention from researchers. However, due to limited capacitance and low energy density, there is still scope for improvement. The race to develop novel methods for enhancing their electrochemical characteristics is still going strong, where the goal of improving their energy density to match that of batteries by increasing their specific capacitance and raising their working voltage while maintaining high power capability and cutting the cost of production. In this light, this paper offers a succinct summary of current developments and fresh insights into the construction of SCs with high energy density which might help new researchers in the field of supercapacitor research. From electrolytes, electrodes, and device modification perspectives, novel applicable methodologies were emphasized and explored. When compared to conventional SCs, the special combination of electrode material/composites and electrolytes along with their fabrication design considerably enhances the electrochemical performance and energy density of the SCs. Emphasis is placed on the dynamic and mechanical variables connected to SCs′ energy storage process. To point the way toward a positive future for the design of high‐energy SCs, the potential and difficulties are finally highlighted. Further, we explore a few important topics for enhancing the energy densities of supercapacitors, as well as some links between major impacting factors. The review also covers the obstacles and prospects in this fascinating subject. This gives a fundamental understanding of supercapacitors as well as a crucial design principle for the next generation of improved supercapacitors being developed for commercial and consumer use. This review gives the insights to enlarge the energy density of a supercapacitor device by doing numerous modifications in electrode materials, electrolytes, design, and fabrication. Overall, it suggests what combinations of electrode materials, electrolytes and designs should be taken into consideration for a high energy density supercapacitor.